Impact of outcome adjudication in kidney disease trials: observations from the Study of Heart and Renal Protection (SHARP) - Herrington, WG; Harper, C; Staplin, N; Haynes, R; Emberson, J; Reith, C; Hooi, LS; Levin, A; Wanner, C; Baigent, C; Landray, M (Elsevier, 2023)
Introduction: We aimed to assess opportunities for trial streamlining and the scientific impact of adjudication on kidney and cardiovascular outcomes in CKD.